PERANCANGAN SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB - Tito Budi Raharto; Teuku Muhammad Fawaati; Oktavia Nilasari (International Research on Big-Data and Computer Technology: I-Robot, 2019)
Libraries are part of the learning resources that should be owned by every school or college. Because learners easily find the information or knowledge through library. With the development of technology make people think to be able to work more effectively and efficiently. One of them is to make the conventional system to a computerized system. The website by utilizing the facilities connected to the internet. libraries can be more effective and efficient in searching and ordering books. In this research, I have designed a web-based information systems using programming languages PHP MySQL. With this system, is expected to address the various needs of the user to search for books and book as well as facilitate the administration in the circulation of borrowing books and preparing reports. From the research that has been conducted on these results the authors implement in Designing Library Information System Web-Based in Lampung Provicial Library.